Effect of three nanobiomaterials on the surface roughness of bleached enamel - Maryam Khoroushi; Farinaz Shirban; Samaneh Doustfateme; Sara Kaveh (Wolters Kluwer Medknow Publications, 2015)
Background: The ever-increasing demand for enhanced esthetic appearance has resulted in significant developments in bleaching products. However, the enamel surface roughness (SR) might be negatively affected by bleaching agents. This in vitro study was undertaken to compare the effects of three nanobiomaterials on the enamel SR subsequent to bleaching. Materials and Methods: The crowns of six extracted intact nonerupted human third molars were sectioned. Five dental blocks measuring 2 mm × 3 mm × 4 mm were prepared from each tooth and placed in colorless translucent acrylic resin. The enamel areas from all the specimens were divided into five groups (n = 6): Group 1 did not undergo any bleaching procedures; Group 2 was bleached with a 40% hydrogen peroxide (HP) gel; Groups 3, 4, and 5 were bleached with a 40% HP gel modified by bioactive glass (BAG), amorphous calcium phosphate, and hydroxyapatite, respectively. The enamel SR was evaluated before and after treatment by atomic force microscopy. The data were analyzed by Kruskal-Wallis and Mann-Whitney tests. Results: SR increased significantly in the HP group. SR decreased significantly in the HP gel modified by BAG group as compared to other groups. Conclusions: Within the limitations of this study, incorporation of each one of the three test biomaterials proved effective in decreasing enamel SR subsequent to in-office bleaching technique.